HUMAN TRAFFICKING DAN SOLUSINYA DALAM PERSPEKTIF HUKUM ISLAM - Basri, Rusdaya (DIKTUM: Jurnal Syariah dan Hukum, 2012)
This article discusses the problem of human trafficking and the solution in the perspective of Islamic law. Human Trafficking is "the act of recruiting, transporting, storage, delivery, transfer, harboring or receipt of persons by threat of violence, the use of violence, kidnapping, abduction, fraud, deception, abuse of power or of a position of vulnerability, or giving entrapment debt payments or benefits to achieve the consent of a person having control over another person, whether committed within the country and between countries, for the purpose of exploitation or lead to the exploitation ". Considering that Human Trafficking is a crime against humanity that can not be tolerated. Appearance has destroyed life aspects, for violation of human rights became the main focus of this discussion with the approach of the literature. A review of the literature suggests that Human Trafficking in the form of slavery has existed since before Islam came even become a tradition in pre-Islamic social system. In the perspective of the social history of Islamic law, trafficking in any form is prohibited in Islam for violating human rights and dignity. And solutions for combating trafficking is transforming the Islamic concept of zakat utilization in addressing trafficking issues in a practical way. It means giving alms directly to the victims of trafficking as a group riqab and utilize zakat as support in funding programs to eradicate trafficking. Besides handling the problem of trafficking, conducted with the efforts and measures of structural and cultural, strategic and practical. Thus, efforts to eliminate trafficking in persons, especially women and children can be realized. Due to the elimination of trafficking in persons is a religious obligation, obligations, liabilities and obligations of all Muslims who respect human dignity and humanity.